2010
DOI: 10.1103/physreva.82.043613
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the superfluid state in a disordered one-dimensional ultracold fermionic gas

Abstract: We study a 1D Fermi gas with attractive short range-interactions in a disordered potential by the density matrix renormalization group (DMRG) technique. Our results can be tested experimentally by using cold atom techniques. We identify a region of parameters for which disorder enhances the superfluid state. As disorder is further increased, global superfluidity eventually breaks down. However this transition seems to occur before the transition to the insulator state takes place. This suggests the existence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
(60 reference statements)
1
25
0
Order By: Relevance
“…Our disordered superfluids are characterized by a certain concentration of pointlike impurities 47,50 , each one of strength V randomly placed along the chain, such that there are sites with impurity V and non-impurity sites (). For each set of parameters, , we generate samples to avoid features due to specific impurity configurations.…”
Section: The Theoretical Model and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our disordered superfluids are characterized by a certain concentration of pointlike impurities 47,50 , each one of strength V randomly placed along the chain, such that there are sites with impurity V and non-impurity sites (). For each set of parameters, , we generate samples to avoid features due to specific impurity configurations.…”
Section: The Theoretical Model and Computational Methodsmentioning
confidence: 99%
“…However, none of the previous studies i) has considered fermionic superfluid systems (with both charge and spin degrees of freedom) and ii) none has found entanglement as an unambiguous signature of the SIT: the typical fingerprints of a quantum phase transition (non-monotonicity, discontinuity or saturation) were missing. Furthermore, important features of the SIT are in current debate, as the existence or not of a critical disorder intensity for localization in 1D and 2D systems 5,4347 , as well as the nature of the transition, whether it is a more pronounced transition or a crossover 6,48 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar kind of quasi-periodic lattice has been already used to study the Anderson localization in Refs. [21][22][23]. Strictly, k 1 /k 2 should an irrational number for the quasi-periodic case, however, by using two coprime positive integers 2k 1 and 2k 2 we can still induce some weak disorder effect as shown in Fig.…”
mentioning
confidence: 98%
“…The density matrix renormalization group analysis of ref. [31] showed that phase coherence in a one dimensional disordered Hubbard model with attractive interactions at zero temperature is enhanced for weak coupling and disorder close to but below the superconductor-insulator threshold. In Refs.…”
mentioning
confidence: 99%